2019
DOI: 10.1111/febs.14931
|View full text |Cite
|
Sign up to set email alerts
|

Putative interaction site for membrane phospholipids controls activation of TRPA1 channel at physiological membrane potentials

Abstract: The transient receptor potential ankyrin 1 (TRPA1) channel is a polymodal sensor of environmental irritant compounds, endogenous proalgesic agents, and cold. Upon activation, TRPA1 channels increase cellular calcium levels via direct permeation and trigger signaling pathways that hydrolyze phosphatidylinositol‐4,5‐bisphosphate (PIP2) in the inner membrane leaflet. Our objective was to determine the extent to which a putative PIP2‐interaction site (Y1006‐Q1031) is involved in TRPA1 regulation. The interactions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 55 publications
2
11
0
Order By: Relevance
“…During the review process, a structural study on TRPA1 was published identifying a direct interaction between N855 and the backbone carbonyl of C1024 from a short predicted C-terminal α-helix located at the cytosol-membrane interface near S1 and S4 of the sensor domain [64]. The findings support our previous predictions [56] and may partly explain our data presented in Figure S4.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…During the review process, a structural study on TRPA1 was published identifying a direct interaction between N855 and the backbone carbonyl of C1024 from a short predicted C-terminal α-helix located at the cytosol-membrane interface near S1 and S4 of the sensor domain [64]. The findings support our previous predictions [56] and may partly explain our data presented in Figure S4.…”
Section: Discussionsupporting
confidence: 88%
“…Previous studies have identified the C-terminal loop as a site for Ca 2+ /calmodulin and phosphatidylinositol-4,5-bisphophate binding [54,56]. Mutations within this region affected TRPA1 responses induced by various stimuli including cinnamaldehyde, allyl isothiocyanate, voltage, Ca 2+ and carvacrol.…”
Section: Modeling the Proximal C-terminal Loopmentioning
confidence: 99%
“…For the experiments described in Figure 1, the extracellular bath solution contained: 140 mM NaCl, 5 mM KCl, 2 mM MgCl 2 , 5 mM EGTA, and 10 mM FIGURE 1 | Acute PIP 2 depletion has an opposite effect on cold-dependent gating of TRPA1 to missense histidine-to-arginine mutation at position 1018. (A) Schematic diagram shows binding of Ca 2+ -CaM (calmodulin) to C terminus of TRPA1 (Macikova et al, 2019). The binding domain for CaM partly overlaps with the proposed binding pocket for PIP 2 (in red) which includes H1018.…”
Section: Electrophysiology and Cold Stimulationmentioning
confidence: 99%
“…The proximal C terminus contains a TRP-like domain that interacts with a pre-S1 helix. There are at least two sites with separate functions from which the activity of TRPA1 can be regulated by membrane phosphatidylinositol-4,5-bisphosphate (PIP 2 ) or other phosphoinositides: the first, formed by the intracellular part of VSLD and contributed to by K989 from the TRP-like domain (Samad et al, 2011;Witschas et al, 2015;Zimova et al, 2018), and the second localized between adjacent subunits (T1003-P1034), capable of directly affecting the gating of the channel through the S4-S5 linker and R975 from the TRP-like domain (Macikova et al, 2019). Mutation at the highly conserved phenylalanine F1020 located in the center of the latter interacting region produced channels with faster activation kinetics and with significantly suppressed responses at negative membrane potentials.…”
Section: Predicted Role Of Phosphoinositides In the Regulation Of Temmentioning
confidence: 99%
See 1 more Smart Citation